Benefits and Challenges of Issuing Municipal Bonds for the Aceh Government - Nadilla, Trie; Ulfah, Almira Keumala; Midesia, Shelly; Fitria, Ana; Sagala, Wahyu Putri (Universitas Muhammadiyah Makassar, 2025)
The issuance of sukuk—Islamic bonds—by local governments has emerged as a viable alternative for financing infrastructure and public development, particularly in regions with special autonomy such as Aceh. This study explores the benefits and challenges of issuing municipal sukuk by the Aceh Government in light of the province’s unique legal framework under Islamic law and the scheduled termination of Special Autonomy Funds by 2027. Using a qualitative library research method, this paper reviews relevant literature, government regulations, and secondary data sources to assess the feasibility of sukuk issuance. The findings reveal several key benefits, including access to more affordable, sharia-compliant financing; reduced dependency on regional budgets and conventional loans; and the promotion of regional financial independence. However, challenges persist, such as limited regulatory clarity, insufficient infrastructure readiness, and low public literacy on sukuk instruments. To maximize the potential of sukuk, policy support, public education, and financial ecosystem strengthening are crucial. The study concludes that sukuk can serve as a strategic financial tool for sustainable development in Aceh, aligning with both economic objectives and Islamic financial principles.